Determination of inosine 5′-monophosphate dehydrogenase activity in red blood cells of thiopurine-treated patients using HPLC - Beringer, Audrey; Citterio-Quentin, Antony; Otero, Rebeca Obenza; Gustin, Clémence; Clarke, Rebecca; Salvi, Jean-Paul; Boulieu, Roselyne (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2017)
Thiopurine drugs are commonly used in immune diseases and to a lesser extent, in transplant rejection prophylaxis: however interindividual variability in drug response and in the occurrence of adverse events is observed. Genetic variation in thiopurine S-methyltransferase (TPMT) doesn’t completely explain the occurrence of all adverse events and drug response variability. The potential implication of other enzymes involved in thiopurine metabolism, such as ITPA, has been investigated over the last decade but little data is available on inosine 5′-monophosphate dehydrogenase (IMPDH) in patients treated with thiopurine drugs. The authors reported a HPLC method to determine IMPDH activity in the red blood cells (RBCs) of thiopurine-treated patients. IMPDH activity was evaluated by enzymatic conversion of inosine 5′-monophosphate (IMP) to xanthosine 5′-monophosphate (XMP). The XMP formed was analyzed on a Luna® NH2 stationary phase, a weak anion exchange phase that exhibits both ionic and hydrophobic properties. XMP was eluted below 15min. Intra-assay and inter-assay precisions were below 9% for RBCs supplemented with 2, 40 and 80μmol/L of XMP. IMPDH activity was measured in adults without thiopurine treatment as well as in adult and paediatric patients treated with thiopurines. A wide interindividual variability in IMPDH activity in RBCs was observed. No difference in IMPDH activity was found between untreated subjects and adult and paediatric patients on thiopurine therapy (median value 11.8, 7.9 and 7.7nmol XPM/g Hb/h respectively). The method described is useful in the determination of IMPDH phenotype from patients on thiopurine therapy and in the investigation of the potential relationship between IMPDH activity in RBCs and the occurrence of adverse events and drug response variability.